Spectroscopic and Biophysical Studies on Chalcones and Schiff Bases Derived from Chromen-2-one and Quinoline-2(1H)-one Derivatives as Antibacterial Agents - Alotaibi, Saad H. (Asian Journal of Chemistry, 2020)
A series of chalcone derivatives and arylidene analogues derived from 3-acetyl coumarin were synthesized. The synthesized compounds were elucidated by spectroscopic analysis such as elemental analysis, infrared, 1H & 13C NMR and mass spectroscopies, and then the synthesized compounds were purified and tested against three bacterial strains. Compound 9c showed high activity against E. coli and P. aeruginosa. Compounds 4 and 6a showed moderate activity against E. coli while compounds 6a, 6b and 9c showed moderate activity against S. aureus. The reference antibiotics were tested against the same bacteria strains in the same conditions and showed that ciprofloxacin have positive activity against P. aeruginosa and S. aureus but it shows negative activity against E. coli while amoxicillin have positive activity against S. aureus and negative activity against E. coli and P. aeruginosa. On the other hand, vancomycin has positive activity against P. aeruginosa but not tested against E. coli and S. aureus. Staph strains were treated with compounds 4 and 7 on DNA fragmentation and DNA cleavage. Docking studies of synthesized compound 9c was determined and the results were compared with ampicillin. Finally, UV and fluorescence analyses of the synthesized compounds (3, 4, 6b, 6c, 6e, 7, 9c and 9e) were also conducted.